NexGen regen? Challenges and opportunities for growth factors and signaling agents in periodontal regeneration at intrabony defects - Maria L. Geisinger (Frontiers Media S.A., 2023)
Regeneration of periodontal tissues that have been destroyed by inflammatory periodontitis involves the initiation of tissue engineering and wound healing of multiple tissues involved in the function of the teeth, including the periodontal ligament, cementum, and alveolar bone. Such regeneration is termed guided tissue regeneration and the unique challenges to reconstruct these tissues involve a complex interplay of cells, signaling molecules, and scaffolds. While traditional guided tissue regeneration treatments have involved cell occlusive membranes, bone replacement graft scaffolds, and endogenous multipotent mesenchymal stem cells, the use of adjunctive materials to enhance healing outcomes has been studied and many such adjunctive factors are in common current clinical use. This report will focus on the current and emerging adjunctive growth factors and signaling molecules that can be used to optimize periodontal regeneration in periodontal intrabony defects, their mechanisms of action, the challenges associated with periodontal regeneration, and future avenues for research.